Physiological Responses of Indigenous Vegetable of Sintrong (Crassocephalum crepidioides) due to Exposure to High Temperature - Utama, Ulfiana Mahira Rahma; Kurniawati, Ani; Faridah, Didah Nur (Universitas Sebelas Maret, 2023)
Sintrong is an Indonesian indigenous vegetable with leaves used for vegetables, digestive disorders, and burns. Changes in the environment due to an increase in temperature affect the growth and quality of sitrong, and its existence in the nature is threatened. This study aims to obtain information about the effect of exposure to high temperatures on the physiological character and flavonoid content of indigenous sintrong vegetables and obtain accession of sintrong, which can be developed as a functional vegetable. The Nested randomized group design was applied with two factors, temperature differences as the main plot and accession as a second plot. Four replications were conducted for each accession in the Cikabayan experimental garden of IPB. The results showed that exposure to high temperatures up to 32 °C increased the speed of flowering age, which was 4.76% and 7.14% faster and showed a high wilting rate of 36.66%, but decreased leaf area index up to 30.30% and 42.42% at the conditions above ambient temperature exposure (control). Flavonoid content did not show any effect due to exposure to high temperatures. The flavonoid content reached 1695.38 and 1834.83 mg QE 100 g-1. Bogor 1 accession showed the best performance so that the plants can be developed for functional vegetables. Based on the research findings, sintrong should be harvested earlier before flowering to obtain high leaf production and good-quality vegetables.